The testing of reinforced profiles and determination of they durability and geometrical properties. - Кухарь, В.В.; Нагнибеда, Н.Н. (Problems of Tribology, 2016)
The paper presents key methods and technologies for the production of reinforcing profiles of open cross-section with the ecological - economic perspective is justified by the rationality of the manufacture of cold - formed steel profiles is the sequential profiling in the rolls method. Were developed method of testing strength and geometric characteristics of the bent profiles with modified configuration. Used standard test equipment and methods graph-analytical determination of physical and geometrical parameters. Geometric and strength characteristics of steel roll-formed profiles with new configura-tion discribed a basic acceptance of the product characteristics. It is describes that the changing profile design does not re-quire significant technology changes, but the geometric deviation are more sensitive to the accuracy of the mill setup.